The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1021/bi3011994
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Determines and Limits rHDL Formation from Human Plasma Apolipoprotein A-II and Phospholipid Membranes

Abstract: Apolipoprotein (apo) A-II, the second most abundant protein after apo A-I of human plasma high-density lipoproteins (HDL), is the most lipophilic of the exchangeable apolipoproteins. The rate of microsolubilization of dimyristoylphosphatidylcholine (DMPC) membranes by apo A-I to give rHDL increases as the level of membrane free cholesterol (FC) increases up to 20 mol % when the level of reaction decreases to nil. Given its greater lipophilicity, we tested the hypothesis that apo A-II and its reduced and carbox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…This feature is mainly determined by the type, proportion, and interaction between lipid and protein cargo [119]. Many of the early structural studies on rHDL/sHDL employed particles reconstituted with dimyristoylphosphatidylcholine (DMPC, a shorter saturated acyl chain PL, 14:0), due to its ability to spontaneously form rHDL/sHDL particles when DMPC vesicles were mixed with apoA-I [120][121][122][123][124][125]. Later, the cholate dialysis method [126] was reported to allow reconstitution of rHDL/sHDL with physiologically relevant phospholipids that have longer and unsaturated acyl chains like palmitoyloleoylphosphatidylcoline (POPC, 16:0-18:1).…”
Section: Hdl-mimetics: Composition and Characteristicsmentioning
confidence: 99%
“…This feature is mainly determined by the type, proportion, and interaction between lipid and protein cargo [119]. Many of the early structural studies on rHDL/sHDL employed particles reconstituted with dimyristoylphosphatidylcholine (DMPC, a shorter saturated acyl chain PL, 14:0), due to its ability to spontaneously form rHDL/sHDL particles when DMPC vesicles were mixed with apoA-I [120][121][122][123][124][125]. Later, the cholate dialysis method [126] was reported to allow reconstitution of rHDL/sHDL with physiologically relevant phospholipids that have longer and unsaturated acyl chains like palmitoyloleoylphosphatidylcoline (POPC, 16:0-18:1).…”
Section: Hdl-mimetics: Composition and Characteristicsmentioning
confidence: 99%
“…The dried lipids were dispersed into TBS by vortexing above 24 C after which the lipids were subjected to three cycles of warming to 50 C with vortexing and freezing to À20 C. rHDL were prepared by incubating DMPC MLV containing 15 mol % FC over night at the transition temperature of the DMPC, 24 C, with a DMPC/apo AI ratio of 10 (w/w). Unbound DMPC was sedimented at 16,000 Â g for 30 min in an Eppendorf 5415C centrifuge (Thermo-Fischer, Waltham, MA) at 4 C. The rHDL in the supernatant were separated into various rHDL by size exclusion chromatography (SEC) over tandem columns of Superose HR6 (GE Healthcare, Pittsburgh, PA) and fractions collected (9,19). The peak fraction for the largest rHDL (1 mL) was collected and analyzed by analytical SEC to ensure purity and document homogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…(28) Others, like us, have observed that the DMPC (0 mol% FC) T m for rHDL (apo A-I) is lower than that of pure DMPC and that the thermal unfolding of apo A-II within rHDL occurs at a lower temperature than that of apo A-I. (29, 30) Moreover, increasing the FC content increases particle size(12, 13, 31) and the negative charge on apo A-I while reducing the free energy of apo A-I α-helix stabilization. (31)…”
Section: Discussionmentioning
confidence: 92%
“…The particle sizes do not increase continuously with increasing mol% FC but rather appear to be quantized so that they occur as discrete species. This has been attributed to an increase in domain size with the addition of FC so that additional apos are needed to fully circumscribe the domain(12, 13) and form a disc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation